MEMAHAMI APA YANG KITA MAKAN: SUATU KERANGKA BERPIKIR MARXIS TERHADAP KOMPOSISI PRODUKSI DALAM SISTEM PANGAN KONTEMPORER - Ramadhan, Rury (Penerbit Lafadz Jaya, 2026)
This article aims to provide a comprehensive understanding of the contemporary food system within its totality. Using a qualitative approach through literature review, the analysis is primarily grounded in Karl Marx’s Capital: A Critique of Political Economy (Volume I) and Eric Holt-Giménez’s A Foodie’s Guide to Capitalism. The discussion focuses on the moment of food production, where food transforms from a mere object of subsistence into a commodity. This transformation constitutes the fundamental basis of the modern food system. The argument is constructed through a causal analytical framework, beginning with the fundamental question of how food is produced, and situating capitalism as the overarching social structure that conditions the entire process. The findings indicate that the capitalist mode of production organizes food production not for direct consumption, but for capital accumulation, resulting in structural contradictions such as hunger amidst abundance. Furthermore, the absence of capitalism as a central analytical variable in contemporary food discourse leads to fragmented and depoliticized food movements that fail to address root causes. This study concludes that a critical understanding of capitalism is an essential prerequisite for any attempt to create a healthy, equitable, and sustainable food system. Without such a perspective, efforts to reform the food system will remain superficial and ineffective in resolving its structural problems.